The Cumacean (Crustacea: Peracarida) Genus Petalosarsia (Pseudocumatidae) from the Pacific Ocean - Akiyama, Tadashi; Gerken, Sarah (Zootaxa, 2012)
The distribution of the cumacean family Pseudocumatidae is restricted to the North Atlantic, Mediterranean and brackishwaters of the Pont-Caspian region, except for three known species of the genus Petalosarsia. The present study describes ninespecies of Petalosarsia from Japanese waters, the Sulu Sea, the North-west Pacific, the Indo-West Pacific, and the Tasman Sea,Australia. The occurrence of P. declivis (Sars, 1865) in northern Hokkaido agrees with the reported circumpolar distribution ofthis species. Four species from the Pacific coast of southern Japan and the East China Sea, P. brevirostris Gamô 1986, P. ovalissp. nov., P. ryukyuensis sp. nov. and P. gamoi sp. nov., are characterized by prominent dorsolateral carinae with teeth anteriorlyand the basis of the 2nd maxilliped with a semicircular plate on the ventral surface. Nine specimens collected from the Sulu Seaincluded five species, P. brevirostris, P. gamoi, P. jonesi sp. nov. P. suluensis sp. nov. and P. longicauda sp. nov. The latterthree species were characterized by no or faint dorsolateral carinae on the carapace. Among them, P. jonesi was similar to P.longirostris from the eastern tropical deep Atlantic. Petalosarsia australis sp. nov. from the Tasman Sea is characterized by onefaint pair of dorsolateral carinae running for the entire length of the carapace. The species richness of Petalosarsia in the SuluSea and the Indo-West Pacific suggests a wide distribution of ancestors of Pseudocumatidae around the ancient Tethys Sea, with the Ponto-Caspian region located near the center. The habitat of Petalosarsia was mostly deeper than 200 m.